An orthography normalizing program for Danish - Molbæk Hansen, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1983)
The paper is a description of a program which transforms Danish orthographic texts into so-called normalized notation, i.e. a format which can serve as input to a text-to-speech-by-rule algorithm which is under development at the institute. The main features of the program are described, and the peculiarities of Danish orthography which motivate these features are presented. The capabilities and the limitations of the program are illustrated, and the possibilities of future improvements and extensions of the program are outlined.